(3NQjOI GdbUQ hLQjOI GdYUQs - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA JQLeI aNQ GdOjf CHj GdeYGdi Hf GdCOjH CHj GdMSf eMeO Hf GdMSf GdhQcGfi Hbhdg (B: (3aUjYkG dGjTa ZHGQg ai GdefGXQI s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeg TeS GdOjf Pi GdHQGYJjf JGL GUagGf Ci GdaJM eMeO Hf Ydi Hf eMeO GdfWfRi s
(3LRA efgG ai TYQGA GdYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJGQjNs